2019
DOI: 10.14744/hnhj.2019.16013
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum sodium level in determining complicated appendicitis risk in children

Abstract: Introduction: Acute appendicitis is one of the most common surgical emergencies in childhood. Early recognition and treatment of children with complicated appendicitis, especially perforated and gangrenous, is very crucial. The aim of the present study was to determine the predictive value of simple blood tests, such as serum sodium (Na) level, C-reactive protein (CRP) level, and blood leukocyte and neutrophil counts, in complicated appendicitis. Methods: A total of 403 patients who underwent operation with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 21 publications
1
30
0
1
Order By: Relevance
“…They concluded hyponatremia was an independent predictor of complicated appendicitis. 6 The literature however is not consistent, with Besli et al 13 showing no association between hyponatremia (defined as sodium <135 mmol/L) and complicated appendicitis in children. They performed a retrospective review including 403 children, hyponatremia was found in 25% (62/245) of children with complicated appendicitis and 18% (29/158) of children with uncomplicated appendicitis (p = 0.103).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They concluded hyponatremia was an independent predictor of complicated appendicitis. 6 The literature however is not consistent, with Besli et al 13 showing no association between hyponatremia (defined as sodium <135 mmol/L) and complicated appendicitis in children. They performed a retrospective review including 403 children, hyponatremia was found in 25% (62/245) of children with complicated appendicitis and 18% (29/158) of children with uncomplicated appendicitis (p = 0.103).…”
Section: Discussionmentioning
confidence: 98%
“…Complicated appendicitis has previously been defined either on the basis of intraoperative findings, which varied between studies 6,11,13 and on histology. 12,13 A recent systematic review suggested future studies investigating hyponatremia in complicated appendicitis should use the cut off of <135 mmol/L, as 135 mmol/L is generally accepted as the lowest normal sodium level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] In another study, it was reported that a high CRP level is a marker with high sensitivity and low specificity in differentiating simple and perforated appendicitis. [22] Besli et al [11] found CRP level >2.81 mg/dL to be a marker with low sensitivity (53.1%) and mean specificity. In our study, when the perforated and non-perforated groups were compared, CRP values were found to be significantly higher in the perforated appendicitis group, and the sensitiv-ity and specificity values were found to be 59.3% and 63.3%, respectively, when the cutoff value was taken as 2.35 mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…[8] However, there are studies that argue the opposite as well. [11] Data on the relationship between perforated appendicitis and hyponatremia in adult patients are very limited. We found three different studies suggesting that hyponatremia may act as a marker in complicated appendicitis during our research.…”
Section: Discussionmentioning
confidence: 99%